Coating of Pd/C catalysts with Lewis-acidic ionic liquids and liquid coordination complexes – SCILL induced activity enhancement in arene hydrogenation - Lijewski, Martin; Hogg, James M.; Swadzba-Kwasny, Malgorzata; Wasserscheid, Peter; Haumann, Marco (RSC Advances, 2017)
New solid catalysts with ionic liquid layer (SCILLs) were prepared by the coating of heterogeneous Pd/C catalysts with a thin film of acidic liquid: a known chloroaluminate ionic liquid (IL), [BMIM]Cl/AlCl3, and a recently developed liquid coordination complex (LCC), urea/AlCl3. Both coatings improved the activity of Pd/C catalyst against toluene hydrogenation; at lower temperatures (40 °C) the IL-SCILL performed better, whereas at 80 °C the LCC-SCILL gave higher conversion. A thin film of ionic liquid proved to be sufficient to increase activity, while larger volumes of ionic liquid resulted in a decrease in activity due to pore blocking and hence mass transport limitations. Kinetic investigations in batch mode revealed a zero order with respect to toluene concentration, a first order in hydrogen pressure, and activation energy of 64.7 kJ mol-1 for the Pd/C catalyst. The SCILL catalysts had slightly lower values of 53.1 kJ mol-1 for [BMIM]Cl/AlCl3 and 61.4 kJ mol-1 for urea/AlCl3, respectively.
EAM Import::2019-03-13

Continuous Gas-Phase Hydroaminomethylation using Supported Ionic Liquid Phase Catalysts - Schneider, Martin; Lijewski, Martin; Woelfel, Rene; Haumann, Marco; Wasserscheid, Peter (Angewandte Chemie International Edition, 2013)
Keywords: amine formation; hydroaminomethylation; hydroformylation; ionic liquids; supported catalysts

Modification of nitrogen doped carbon for SILP catalyzed hydroformylation of ethylene - Weiß, Alexander; Giese, Matthias; Lijewski, Martin; Franke, Robert; Wasserscheid, Peter; Haumann, Marco (Catalysis: Science and Technology, 2017)
We report the application of nitrogen doped carbon (NDC) materials as supports for the SILP catalyzed gas-phase hydroformylation of ethylene. The Rh-xantphos complex, dissolved in [EMIM][NTf2] and dispersed onto commercially available activated carbon yielded low activity. The incorporation of nitrogen functionalities into the surface was achieved via oxidation of the original carbon support followed by reduction with either urea or ammonia. SILP catalysts based on the so-obtained NDC materials provided higher activity in ethylene hydroformylation, while at the same time the formation of undesired aldol condensation products was low. Thus, the performance of the new SILP catalyst on NDC material represents a significant step ahead for a technically relevant, continuous catalytic operation with very high aldehyde selectivity.
CRIS-Team Scopus Importer:2023-03-29